Spiritual Gift Inventories: Validity & Function - Hathaway, William Lloyd (Journal of psychology and christianity, 2018)
Spiritual gift inventories have become widely used by Christians to discover or confirm spiritual gifts. The inventories all have either implicit or explicit theologies of spiritual gifts and their function in Christian life. A brief overview of the biblical and systematic theology pertaining to spiritual gifts is offered to determine the conceptual features of the underlying spiritual gifts concept that any purported inventory would have to track to constitute a construct-valid measure. Attention is given to taxonomies of spiritual gifts, biblical terminology relevant to a theology of spiritual gifts, and theological debates over whether at least some "miraculous" or "revelatory" gifts are still present in the body of Christ today. Several of spiritual gift inventories report at least some psychometric data about their reliability and validity. Yet the few focused studies of the psychometric quality of scales that have been attempted have not supported their validity either as a measure of their author's model of spiritual gifts or of the models themselves. The paper concludes with suggestions for how a biblically congruent, theologically informed, and psychometrically competent approach to spiritual gifts may move forward.